Declines in Dietary Iron Absorption Following Simulated Military Operations Are Exacerbated by Energy Deficit. (29th May 2020) - Hennigar, Stephen; Hatch-McChesney, Adrienne; Allen, Jillian; Carrigan, Christopher; Murphy, Nancy; Karl, J Philip; Gwin, Jessica; Margolis, Lee; McClung, James; Pasiakos, Stefan
Abstract: Objectives: Iron status declines with military training; however, the reason for the decline is not known. The objective of this study was to determine whether dietary iron absorption is reduced following military training and whether energy deficit during training modifies the effect. Methods: This was a randomized, cross-over, controlled-feeding trial in healthy, active duty military males (n = 10, age 22.4 ± 5.4 y, weight 87.3 ± 10.9 kg) with normal iron status (serum ferritin 77.0 ± 36.7 ng/mL). Following a rest day (no exercise), participants completed a 72-h simulated sustained military operations (SUSOPS) followed by a 7-d recovery period. SUSOPS was comprised of military tasks designed to elicit high energy expenditures, muscle damage, and sleep deprivation. During SUSOPS, participants were randomized to consume ± 10% of estimated total daily energy expenditure (BAL) or 45% of total daily energy expenditure to induce severe negative energy balance (NEG BAL), but an equivalent amount of dietary iron. Two hours after rest, BAL, and NEG BAL participants consumed a beverage containing 3.8 mg of a stable iron isotope and plasma isotope appearance and hepcidin were determined 0, 20, 40, 60, 120, 240, and 360 min later. Results: BAL maintained weight (−0.03 ± 0.8 kg) and muscle glycogen (4.1 ± 68.1% change), while NEG BAL lost weight (−2.38 ± 1.7 kg, P  < 0.01) and muscle glycogen (−47.6 ± 17.8% change, P  = 0.08) during SUSOPS. C-reactive protein (rest 1.2 ± 0.9, BAL 4.7 ± 3.6, NEG BAL 4.8 ± 3.5 mg/L, Pphase < 0.001) increased with SUSOPS compared to rest regardless of energy balance. Peak plasma isotope appearance at 120 min was 49% lower with BAL (116.9 ± 81.4% change from 0 min) and 74% lower with NEG BAL (58.9 ± 38.1%) compared to rest (229.7 ± 97.3%, P  < 0.01 for all comparisons). Plasma hepcidin was not different at 0 min (rest 7.2 ± 1.6, BAL 6.7 ± 2.4, NEG BAL 6.8 ± 1.7 ng/mL, P  = 0.79) and peaked at 360 min (rest 19.4 ± 9.5, BAL 9.5 ± 4.7, NEG BAL 13.7 ± 8.9 ng/mL, P  = 0.03). Conclusions: Dietary iron absorption is reduced following SUSOPS in healthy males with normal iron status and the reduction is exacerbated with energy deficit. Circulating concentrations of hepcidin following 72-h SUSOPS do not appear to mediate the reduction in dietary iron absorption. Funding Sources: The views expressed are those of the authors and do not reflect official policy of the Army, DoD, or US Government. Supported by MRDC.